1997
DOI: 10.1161/01.cir.96.11.3954
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Type 2 Receptors Are Reexpressed by Cardiac Fibroblasts From Failing Myopathic Hamster Hearts and Inhibit Cell Growth and Fibrillar Collagen Metabolism

Abstract: These findings demonstrate that AT2-R is re-expressed by cardiac fibroblasts present in fibrous regions in failing CM hearts and that the increased AT2-R exerts an anti-AT1-R action on the progression of interstitial fibrosis during cardiac remodeling by inhibiting both fibrillar collagen metabolism and growth of cardiac fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
177
1
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(189 citation statements)
references
References 42 publications
7
177
1
4
Order By: Relevance
“…5,6,7,9 The AT 1 cellular receptor site appears to mediate most of the known actions of angiotensin II, although a second receptor site exists, AT 2 , 10 which appears to play an important role in apoptosis 11 and inhibition of cell growth and fibrillar collagen metabolism. 12 Valsartan is a new orally active angiotensin II antagonist which inhibits the RAS by selectively preventing the interaction of angiotensin II at its AT 1 cellular receptor site 9,13 Previous Phase I trials with valsartan have shown it to be well tolerated in single doses ranging from 10 to 400 mg once daily. 14 Adverse experiences reported in these trials were of mild-to-moderate intensity, generally self-limiting and judged unlikely to be related to valsartan.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7,9 The AT 1 cellular receptor site appears to mediate most of the known actions of angiotensin II, although a second receptor site exists, AT 2 , 10 which appears to play an important role in apoptosis 11 and inhibition of cell growth and fibrillar collagen metabolism. 12 Valsartan is a new orally active angiotensin II antagonist which inhibits the RAS by selectively preventing the interaction of angiotensin II at its AT 1 cellular receptor site 9,13 Previous Phase I trials with valsartan have shown it to be well tolerated in single doses ranging from 10 to 400 mg once daily. 14 Adverse experiences reported in these trials were of mild-to-moderate intensity, generally self-limiting and judged unlikely to be related to valsartan.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent studies, mostly in cellular and adult animal models, mapped the distribution of AT 2 R in certain areas of the brain, 3 kidneys, 4 coronary arteries, cardiomyocytes, ventricular myocardium, 5 and the vasculature. 6,7 Increased AT 2 R expression has been observed under pathological conditions, such as vascular injury, 8 hypertension, 6,7 myocardial infarction, 9,10 congestive heart failure, 11 renal failure, 12 and brain ischemia. 13 Few studies have investigated the functional expression of AT 2 R in humans.…”
mentioning
confidence: 99%
“…In agreement with this idea, Stoll et al (1995) first reported that AT 2 receptor activation inhibits the proliferation of endothelial cells. The antiproliferative action of the AT 2 receptor was also documented in VSMC (Nakajima et al, 1995), PC12W pheochromocytoma cells (Meffert et al, 1996), renomedullary cells (Maric et al, 1998), and cardiac fibroblasts (Ohkubo et al, 1997). Comparison of embryonic VSMC cultures from wild-type and AT 2 receptor null mice further indicated that AT À 2 cells display an exaggerated proliferative response to serum .…”
Section: Introductionmentioning
confidence: 89%